Data-driven modeling of phosphorus (P) dynamics in low-P stormwater wetlands. (August 2019) - Juston, John M.; Kadlec, Robert H.
Abstract: The ability to simulate wetland phosphorus (P) concentration dynamics in the low-P domain (<20 μg/L of total P) has been poor. This paper develops a new model algorithm to describe P removal in Stormwater Treatment Areas (STAs) for Everglades restoration. It includes a performance review of previous low-P models. Analysis of inflow-outflow pulse responses at daily and monthly time steps in the STAs revealed surprisingly counterintuitive dynamics (lowest outflow concentrations occurring during highest flow events). Analysis of internal P concentration and flux data (from within STAs) informed new flow-dependent P removal and zero-order return flux formulations. The resulting parsimonious model is based directly on these two core equations. Calibration and testing are presented, using four independent datasets (6–36 month duration) including outflow P time series and internal water treatment profiles. This data-driven approach significantly improved dynamic simulations (R 2  = 0.4–0.7) and identified the determinant role of internal P loading in low-P wetlands. Highlights: To date, no model has been able to capture very low wetland P concentration dynamics (<20 μg/L). One reason is that observed pulse response dynamics in this range are rather counterintuitive. Recent internal wetland data provides new insight on how these dynamics are generated. A new parsimonious model captures observed data (R 2  = 0.4–0.7) including internal water P profiles. A major conclusion is that internal P loading is a main determinant of low-P wetland concentrations.